Charge density analysis attending bond torsion: A bond bundle case study. Issue 24 (6th September 2018) - Goss, Jordan; Wilson, Tim; Morgenstern, Amanda; Eberhart, Mark
Abstract: For nearly a century chemical understanding has been tied to the properties of bonds, although more often than not, these bond properties are rooted in molecular orbital or valence bond representations of the electronic structure. Technological advances, however, are allowing for experimental measurements of the density via high resolution X‐ray diffraction, while theoretical insights are opening the door to its direct calculation using fast and potentially versatile orbital free DFT methods. Capitalizing on these emerging tools without sacrificing orbital derived understanding has spurred a search for density based representations that deliver the same information available from the orbital perspective. We show that recent extensions of the QTAIM formalism are useful as a means of recovering some of the bond properties that have become an intrinsic part of our chemical understanding. Specifically, we compute from the density the changing bond order and bond order distribution accompanying the rotation about a double bond using the well‐studied fulvene molecule as a test case. We compare the picture that emerges from this density based perspective with that stemming from molecular orbital approaches and argue that the two viewpoints are compatible. Abstract : The evolution of molecular orbitals accompanying a chemical process provides valuable insight as to the mechanisms and barriers to charge redistribution. Here, it is shown that the same type of information can be seen in the bond order distribution or extracted by partitioning the charge density—as obtained by any computational or experimental method—into bond bundles and following their progression along a reaction coordinate. Extending this technique to more complex systems will supplement traditional views of reactivity with an orbital free perspective.